(x, y) = (6, -6)
Divide the first equation by 2 to get equal and opposite coefficients for x.
... -2x -y = -6
Add this to the second equation to eliminate x.
... (2x +4y) +(-2x -y) = (-12) +(-6)
... 3y = -18 . . . . . . . . simplify
... y = -6 . . . . . . . . . . divide by 3
Substitute this vaue into any of the equations to find x. We choose to use the reduced first equation above.
... -2x -(-6) = -6
... -2x = -12 . . . . subtract 6
... x = 6 . . . . . . . divide by -2
The solution to the system is (x, y) = (6, -6).